New Approaches to Produce Large‐Area Single Crystal Thin Films. Issue 4 (18th November 2022) - Kim, Geonwoo; Kim, Dongbeom; Choi, Yoonsun; Ghorai, Arup; Park, Gyeongbae; Jeong, Unyong
Abstract: Wafer‐scale growth of single crystal thin films of metals, semiconductors, and insulators is crucial for manufacturing high‐performance electronic and optical devices, but still challenging from both scientific and industrial perspectives. Recently, unconventional advanced synthetic approaches have been attempted and have made remarkable progress in diversifying the species of producible single crystal thin films. This review introduces several new synthetic approaches to produce large‐area single crystal thin films of various materials according to the concepts and principles. Abstract : This review introduces novel synthetic strategies to produce large‐area single crystal thin films of various materials and discusses the technological challenges of dealing with the isostructured crystals (3D materials such as metals, III‐V semiconductors, oxide perovskites, halide perovskites, organic semiconductors) and anisotropic crystals (2D materials such as graphene, hBN, and metal chalcogenides).